The relationship between chest tube size and clinical outcome in pleural infection. - Rahman, N; Maskell, N; Davies, C; Hedley, E; Nunn, A; Gleeson, F; Davies, R (2010)
BACKGROUND: The optimal choice of chest tube size for the treatment of pleural infection is unknown, with only small cohort studies reported describing the efficacy and adverse events of different tube sizes. METHODS: A total of 405 patients with pleural infection were prospectively enrolled into a multicenter study investigating the utility of fibrinolytic therapy. The combined frequency of death and surgery, and secondary outcomes (hospital stay, change in chest radiograph, and lung function at 3 months) were compared in patients receiving chest tubes of differing size (chi(2), t test, and logistic regression analyses as appropriate). Pain was studied in detail in 128 patients. RESULTS: There was no significant difference in the frequency with which patients either died or required thoracic surgery in patients receiving chest tubes of varying sizes ( < 10F, number dying or needing surgery 21/58 [36%]; size 10-14F, 75/208 [36%]; size 15-20F, 28/70 [40%]; size > 20F, 30/69 [44%]; chi(2)trend, 1 degrees of freedom [df] = 1.21, P = .27), nor any difference in any secondary outcome. Pain scores were substantially higher in patients receiving (mainly blunt dissection inserted) larger tubes ( < 10F, median pain score 6 [range 4-7]; 10-14F, 5 [4-6]; 15-20F, 6 [5-7]; > 20F, 6 [6-8]; chi(2), 3 df = 10.80, P = .013, Kruskal-Wallis; chi(2)trend, 1 df = 6.3, P = .014). CONCLUSIONS: Smaller, guide-wire-inserted chest tubes cause substantially less pain than blunt-dissection-inserted larger tubes, without any impairment in clinical outcome in the treatment of pleural infection. These results suggest that smaller size tubes may be the initial treatment of choice for pleural infection, and randomized studies are now required. TRIAL REGISTRATION: MIST1 trial ISRCTN number: 39138989.